Three-faced Brahmani figure - Temples of India Project Team (Jio Institute, 2024)
Adjacent to the inner stairways, Brahmani is depicted with three faces, seated on her pedestal. While her frontal face has sustained damage, the other two faces remain well-preserved. The right face displays a gentle smile. In her upper left hand, she holds a putaka (water vessel), while her upper right hand, although broken, likely once held a shruka (sacrificial ladle). The lower left hand grasps a kamandalu (water pot), and the lower right hand is extended in varada hasta (boon-giving gesture). Adorned with a broad necklace and various other ornaments, Brahmani is accompanied by her vahana (mount), which is visible at the bottom right.